(untitled) (Fiep Bulletin - online, 2012)
The host is the act of receiving, meet, greet you in a qualified manner addressing their needs, putting a willingness to listen and answer qualifying questions. This study aims to investigate the users’ perception of the Family Health Strategy with the host rating. This is an exploratory descriptive research with quantitative approach carried out in the city of Lucena / PB in August 2011 with a sample of 20 people attended the Family Health Unit. One checked that most of the interviewed ones affirmed that the realization of the welcome is frequent in the USF; they like in the form that the welcome is carried out by the professionals of the USF; the realization of the welcome is important in the USF; they receive the welcome for a quicker presence; they carry out the welcome like respected form; they carry out the welcome according to the gravity to the health; and difficulties of the welcome with classification of risk by the professionals of the USF. are ended that the practice of the welcome starts to be of great importance in the Unity of Health of the Family because of attending the users respecting his complaint of health, as well as attending with resolutionable his necessities.